Herbivore-induced GABA signaling suppresses host plant growth to stabilize leaf-tie shelters - Gisuk Lee; Bo Eun Nam; Min-Soo Choi; Hangah Lim; Sang-Gyu Kim; Youngsung Joo (Plant Stress, 2025)
Plants can perceive and respond to herbivore-derived signals not only by activating defenses, but also by altering growth. Some herbivorous insects also manipulate plant traits to construct shelters for predator avoidance. However, how plants respond physiologically to such manipulation remains poorly understood. We investigated the shelter-building caterpillar Elophila turbata and its host plant Lemna minor. Using metabolomics, transcriptomics, hormone profiling, and predation assays, we explored how insect-derived cues influence host plant growth and structure. We show that caterpillar regurgitant and silk induce sustained accumulation of γ-aminobutyric acid (GABA) in host fronds, leading to significant growth suppression. This response was independent of jasmonic acid signaling and associated with upregulation of genes involved in stress responses, growth inhibition, and amino acid metabolism. Predation assays revealed that compact shelters, formed through suppressed growth, reduced detection and attack by aquatic predators. Our findings uncover a novel GABA-dependent plant response to herbivore-derived cues that modulates host architecture and enhances herbivore survival. This work expands our understanding of plant signaling in biotic interactions and highlights growth suppression as a functional outcome of herbivore-induced manipulation.